1994
DOI: 10.1111/j.1464-410x.1994.tb07113.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent symptoms of urinary tract infection in eight patients with refluxing ureteric stumps

Abstract: A dual approach is recommended when complete excision of the kidney and ureter is required. Symptoms of pyelonephritis are not pathognomonic of parenchymal infection but reflect infection above the vesico-ureteric junction. The distinction between supra-junctional and infra-junctional urinary tract infections seems more appropriate and is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 2 publications
0
27
0
1
Order By: Relevance
“…They concluded that the refluxing ureteral stump had a low morbidity. On the other hand, Persad et al [2] stated negative results. They reported the follow-up results of 8 patients with refluxing ureteric stumps, who presented with recurrent urinary tract infections.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…They concluded that the refluxing ureteral stump had a low morbidity. On the other hand, Persad et al [2] stated negative results. They reported the follow-up results of 8 patients with refluxing ureteric stumps, who presented with recurrent urinary tract infections.…”
Section: Discussionmentioning
confidence: 89%
“…On this point, controversies arise regarding further management of the distal refluxing ureteral remnant. There have been advocates [2,8,9] for complete removal of ureteral remnant. Recently, two subsets of studies on management of the persistent ureteral stumps following nephrectomy for a vesicoureteral reflux have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Belman et al 16 proposed that EUS should be ligated if UR is diagnosed in an ectopic ureter before surgery. Persad et al 17 A complete excision of EUS could be necessary only in case of sCUD with concomitant ureteral cancer. To date, only one case of ureteral cancer associated to CUD has been described in an adult patient.…”
Section: Discussionmentioning
confidence: 99%
“…Many technique are described to perform nephrouretectomy from open approach to laparoscopic or retroperitoneoscopic surgery. Therefore one of the measures of nephroureterectomy is the complete removal of ureter at its base to reduce risk of a distal ureteral stump and urinary infections (1). Because of this Literature recommends dual approach with complete excision of the kidney and ureter (2).…”
Section: Discussionmentioning
confidence: 99%